Identification of a ubiquitin-binding domain protein, CD2AP, in predicting the prognosis and treatment of lung adenocarcinoma - Dai, Qinjin; Li, Li; He, Mingfeng; Huang, Jin; Bo, Zhixiang; Yin, Jishan; Ye, Ying (Frontiers in Immunology, 2025)
BackgroundLung adenocarcinoma remains a leading cause of cancer mortality, necessitating novel prognostic biomarkers and therapeutic targets. Ubiquitination, a crucial post-translational modification, is deeply implicated in tumourigenesis. This study aims to identify key ubiquitination-related regulators in LUAD and investigate their clinical significance, with a particular focus on CD2AP.MethodsWe analysed transcriptomic data from TCGA and GEO databases to identify survival-related ubiquitination genes. Proteomic data from the CPTAC database validated key findings. Functional enrichment, immune cell infiltration, and single-cell RNA sequencing (scRNA-seq) analyses were performed to explore the role of CD2AP. Drug sensitivity and molecular docking were used to identify potential therapeutics. Experimental validation included qPCR, Western Blot, immunofluorescence, and functional assays in A549 cells.ResultsCD2AP was identified as a central regulator, with its mRNA and protein levels significantly elevated in LUAD tissues, and this elevation was associated with poor survival. CD2AP expression correlated with TMB, immune infiltration (particularly monocytes/macrophages), and advanced T stage. scRNA-seq confirmed CD2AP enrichment in monocytes and revealed enhanced communication between CD2AP+ tumour cells and monocytes. Two drugs, afatinib and dasatinib, were identified as potential CD2AP-targeting agents via molecular docking. Functional experiments confirmed that silencing CD2AP significantly suppressed the proliferation and migration of A549 cells.ConclusionsOur study identifies CD2AP as a key oncoprotein in LUAD. Our findings suggest that targeting CD2AP represents a promising therapeutic strategy for patients with LUAD. Integrating CD2AP assessment into clinical practice may enhance personalised treatment planning and prognostic evaluation for patients with LUAD.